Profiles of antibiotic- and heavy metal-related resistance genes in animal manure revealed using a metagenomic analysis - Chong Liu; Guichun Li; Xiaobo Qin; Yansheng Xu; Jiarui Wang; Guosheng Wu; Huabing Feng; Jing Ye; Changxiong Zhu; Xiaohua Li; Xiangqun Zheng (Ecotoxicology and Environmental Safety, 2022)
Farmed animals produce excrement containing excessive amounts of toxic heavy metals as a result of consuming compound feed as well as receiving medical treatments, and the presence of these heavy metals may aggravate the risk of spreading drug-resistance genes through co-selection during manure treatment and application processes. However, research on the association between heavy metals and antimicrobial resistance is still lacking. In this study, metagenomic sequencing was used to explore the effects of the co-selection of environmentally toxic heavy metals on the resistome in manure. A relevance network analysis showed that metal-resistance genes (MRGs), especially for copper (Cu) and zinc (Zn), were positively correlated with multiple types of antibiotic-resistance genes (ARGs) and formed a complex network. Most bacteria that co-occurred with both MRGs and ARGs simultaneously are members of Proteobacteria and accounted for 54.7% of the total microbial species in the relevance network. The remaining bacteria belonged to Firmicutes, Bacteroidetes and Actinobacteria. Among the four phyla, Cu- and Zn-resistance genes had more complex correlations with ARGs than other MRG types, reflecting the occurrence of ARG co-selection under the selective pressure of high Cu and Zn levels. In addition, approximately 64.8%, 59.1% and 68.4% of MRGs that correlated with the presence of plasmids, viruses and prophages, respectively, are Cu- or Zn-resistant, and they co-occurred with various ARGs, indicating that mobile genetic elements participate in mediating ARG co-selection in response to Cu and Zn pressure. The results indicated that the use of heavy-metal additives in feed induces the increases of drug resistance genes in manure through co-selection, aggravating the risk of antimicrobial resistance diffusion from animal farm to manure land applications.